Drying and osmotic conditioning in Hancornia speciosa Gomes seeds - Tathiana Elisa Masetto; Silvana de Paula Quintão Scalon (Floresta e Ambiente)
Hancornia speciosa is a native tree species of the Brazilian Cerrado whose seeds are desiccation sensitive. In this study, we aimed to evaluate drying and osmotic conditioning in H. speciosa seeds. We used fresh seeds with 48% moisture content, which were slowly dried until they attained contents of 20%, 15%, 10% and 5%. To evaluate osmotic conditioning, the seeds were imbibed in 12 mL osmotic solutions at 0.0; -0.2; -0.4 and -0.6 MPa for two days. After that, they were dehydrated until their original moisture content. The experiments were carried out in a completely randomized design with four repetitions with 50 seeds each. Reduction in moisture content from 20% to 5% decreased the physiological potential of seeds. H. speciosa seeds do not require osmotic priming with PEG solutions, because imbibition of seeds in osmotic solutions of up to -0.6 MPa results in reduction of germination rate and seedling length.